THE NARRATOR AND THE SPACE IN EDGAR ALLAN POE AND JEAN EPSTEIN - de Oliveira, Laura Lopes (Laboratório Editorial FCL-UNESP, 2012)
The aim of this article is to analyze the role of the narrator, the space and the cinematographic resources in “The fall of the house of Usher” (1839) by Edgar Allan Poe and “La chute de la Maison Usher” (1928) by Jean Epstein.